2015
DOI: 10.1021/acsphotonics.5b00314
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field-Driven Shifting and Expansion of Photonic Band Gaps in 3D Liquid Photonic Crystals

Abstract: Highly tunable 3D liquid photonic crystals are demonstrated using low-dc-field-driven polymer-stabilized blue-phase liquid crystals. The central wavelength of the photonic band gap can be reversibly shifted to more than 200 nm away from the original position. Besides, by controlling the polymerization-induced morphology variations, the band gap can also be expanded from a bandwidth of around 30 nm to at least 310 nm, the first time a “white” blue phase is observed. Both types of band-gap modulation, namely, sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…Under DC field, the polymer fibrils was pulled toward the cathode, stretching the structure near the anode and compressing the structure near cathode simultaneously, thus bandwidth broadening inevitably can be observed. [15,21a] Distinguishingly here, the electrically responsive behavior is dependent on the polarity of DC bias, indicating the nonhomogenous distribution of inherent polymer properties. [21d] On account of the natural UV absorptivity of liquid crystal constituents, intensity gradient of UV light can occur along the incident direction perpendicular to the substrate .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Under DC field, the polymer fibrils was pulled toward the cathode, stretching the structure near the anode and compressing the structure near cathode simultaneously, thus bandwidth broadening inevitably can be observed. [15,21a] Distinguishingly here, the electrically responsive behavior is dependent on the polarity of DC bias, indicating the nonhomogenous distribution of inherent polymer properties. [21d] On account of the natural UV absorptivity of liquid crystal constituents, intensity gradient of UV light can occur along the incident direction perpendicular to the substrate .…”
Section: Resultsmentioning
confidence: 91%
“…Moreover, the facile fabrication process enabled the large‐scale production of the 3D RPCs. Remarkably, it has been reported that distributed feedback can be realized in three dimensions of BP system,[13a] as well as the PBG in each dimension of PSBP can be modulated independently of the others by DC field . Thus, the arbitrarily manipulation of the PBG by polarity or intensity of DC field in either dimension is of significant importance to develop 3D tunable laser.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, many studies have been devoted to clarify the phase structure of BP, both theoretically and experimentally . Moreover, soft matter features of BPs render them responsive to external stimuli, such as temperature, electric field, and light, resulting in tunable performance of BP‐based photonic devices.…”
mentioning
confidence: 99%
“…Figure 4 presents the images of the BPLC microlens array, which was placed under crossed polarizers and operated with different voltages at 38.5 °C. When a reasonable voltage is applied to the sample, the BPLC microlens exhibits a color change due to the electrostriction effect [28]. At a voltage of 50 V, the effective electric field at the edge of the microlens is stronger than that at the center.…”
Section: Methodsmentioning
confidence: 99%